ANALYSIS OF CONSTRUCTION SAFETY RISK MANAGEMENT BASED ON PU MEMORY NUMBER 10 THE YEAR 2021 " CASE STUDY: PROVISION OF SANITATION FACILITIES IN INSTITUTIONS RELIGIOUS EDUCATION" - Assegaf, Syarifah Thahirah; Pramadita, Suci; Jati, Dian Rahayu (Jurnal Teknik Sipil, 2023)
Due to workers' lack of awareness regarding the implementation of Occupational Health and Safety (OHS) in the workplace, the level of work safety in Indonesia still needs to be higher. Construction projects require effective risk management in order to reduce workplace accidents. The construction project for the provision of sanitation facilities and infrastructure at religious education institutions works on the construction of the bathroom, latrines, toilets, ablution facilities, hand washing facilities, and clothes washing facilities, as well as a domestic wastewater treatment plant (WWTP). This study aims to identify hazards based on the project under study, analyze the OHS risk assessment based on the Minister of Public Works Regulation No. 10 of 2021, and analyze the hazards and risk control efforts at each project stage. The result of this study showed that there are 78 risks found in 9 stages of work. Based on the risk assessment of the project under study, two levels of risk were identified, namely low risk and medium risk. A score of a moderate risk level of 6.57 was found in the installation of fabricated WWTP that showed injury risk due to materials and equipment at the Al-Muttaqin Islamic Boarding School, Mubarak Islamic Boarding School, and Darul Hidayah Islamic Boarding School, falling risk due to uneven surface conditions in the Pondok Pesantren Darul Ihsan Islamic Boarding School and the risk of falling into a dug hole at the Nahdotus Shibiyan Islamic Boarding School.